Becoming a mother when suffering from a chronic illness - Riazuelo, Hélène (Frontiers in Psychiatry, 2023)
The critical period of parenthood when facing serious health problems constitutes a major public health issue. The disease may interfere with, influence and compound the difficulties experienced over the course of pregnancy and during the parenthood processes. These processes are to be understood as a passage involving so many changes and fraught with difficulties leading to a series of psychological mobilizations. Illness also needs to be considered as a moment of transition, sometimes of rupture, marking the lives of the people concerned in a more or less lasting way. Various developments are possible, some of which can be envisaged as leading to more positive outcomes, while others appear as if frozen or doomed to failure. Clinical data and method: [See below] Main considerations on the psychotherapeutic treatment: We regularly observe people who find it impossible to muster the internal resources that would enable them to deal with the trials they undergo in such situations. For the psychologist, there is a need to listen in to archaic remnants. Little by little, in the space of psychotherapeutic work, possibilities of “reanimation” of the psyche emerge, an internal space that renews phantasmic activity as it begins to be able to project into the external space and into the space of the sessions.